A column study on removal of chemical oxygen demand (COD), ammoniacal nitrogen, sulfate and turbidity using limestone and activated carbon - Nur Hazirah, Mohd Ridzwan (Universiti Malaysia Perlis (UniMAP), 2013)
Access is limited to UniMAP community.